Isolation and phylogenetic analysis of sindbis viruses from mosquitoes in Germany - Jöst, Hanna; Storch, Volker; Becker, Norbert (Journal of clinical microbiology, 2010)
A molecular survey of 16,057 mosquitoes captured in Southwest Germany during the summer of 2009 demonstrated the presence of Sindbis virus (SINV) in Culex spp. and Anopheles maculipennis sensu lato. Phylogenetic analysis of the German SINV strains linked them with Swedish SINV strains, the causative agent of Ockelbo disease in humans.